Cetuximab intensifies cisplatin-induced testicular toxicity. Issue 1 (July 2016) - Levi, Mattan; Popovtzer, Aron; Tzabari, Moran; Mizrachi, Aviram; Savion, Naphtali; Stemmer, Salomon M.; Shalgi, Ruth; Ben-Aharon, Irit
Abstract: Epidermal growth factor receptor (EGFR) has proliferative properties in the testis. Cetuximab, an anti-EGFR, is administered together with chemotherapy to patients with various types of cancer. This studies aim was to investigate the effect of cetuximab on testicular function. Adult male mice were injected with cetuximab (10 mg/kg), cisplatin (8 mg/kg) or a combination of both, and killed one week or one month later. The doses were chosen by human equivalent dose calculation. Testicular function was evaluated by epididymal-spermatozoa total motile count and sperm motility, weights of testes and epididymides, and the level of anti-Müllerian hormone (AMH) in the serum. Immunohistochemistry was performed to examine germ cell proliferation (Ki-67), apoptosis (Terminal transferase-mediated deoxyuridine 5-triphosphate nick-end labelling), reserve (DAZL-Deleted in azoospermia-like, Promyelocytic leukaemia zinc-finger), blood vessels (CD34) and Sertoli cells (GATA-4). Administration of cetuximab alone increased testicular apoptosis and decreased epididymal-spermatozoa total motile count over time. When added to cisplatin, cetuximab exacerbated most of the recorded testicular parameters, compared with the effect of cisplatin alone, including testis and epididymis weights, epididymal-spermatozoa total motile count, AMH concentration, meiosis and apoptosis. In conclusion, cetuximab has only a mild effect on testicular reserve, but when added to cisplatin, it exacerbates cisplatin-induced testicular toxicity.